2011
DOI: 10.1074/jbc.m111.221382
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Community-associated Methicillin-resistant Staphylococcus aureus Is Caused by Phenol-soluble Modulin Derivatives

Abstract: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) are causing an ongoing pandemic of mostly skin and soft tissue infections. The success of CA-MRSA as pathogens is due to a combination of antibiotic resistance with high virulence. In addition, it has been speculated that CA-MRSA strains such as the epidemic U.S. clone USA300 have increased capacity to colonize human epithelia, owing to bacteriocin-based bacterial interference. We here analyzed the molecular basis of antimicrobial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
142
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(149 citation statements)
references
References 40 publications
3
142
4
Order By: Relevance
“…Antimicrobial Activity of PSM Derivatives-Otto and colleagues (11) suggested that PSM derivatives might serve antimicrobial functions relevant for CA-MRSA niche establishment. To this end, we set up S. aureus bacterial-bacterial interactions, first with the common skin microbe S. epidermidis and second with a leading human skin pathogen, GAS.…”
Section: Imaging Mass Spectrometry Of Ca-mrsa-mentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial Activity of PSM Derivatives-Otto and colleagues (11) suggested that PSM derivatives might serve antimicrobial functions relevant for CA-MRSA niche establishment. To this end, we set up S. aureus bacterial-bacterial interactions, first with the common skin microbe S. epidermidis and second with a leading human skin pathogen, GAS.…”
Section: Imaging Mass Spectrometry Of Ca-mrsa-mentioning
confidence: 99%
“…More recently, the same investigators determined the existence of truncated forms of PSMs with antimicrobial activity against other Gram-positive bacteria. It was proposed that the truncated PSMs contribute to CA-MRSA niche establishment by providing a competitive advantage over other microflora, thereby allowing skin colonization, which predisposes to subsequent soft tissue infection (11).…”
mentioning
confidence: 99%
“…proteolytically processed PSMα1 and PSMα2 peptides show antimicrobial activity and 31 interfere with competing colonizing pathogens (Joo, Cheung et al 2011). Finally, they 32 appear to contribute to the structuring of biofilms during S. aureus infection (Periasamy, (Periasamy, Chatterjee et al 2012).…”
mentioning
confidence: 99%
“…PSMs are of particular interest because they perform multiple roles in pathogenesis. These short peptides compound pathogenicity by activating host receptor-mediated inflammatory responses (12)(13)(14)(15)(16)(17), lysing red and white blood cells (16,18,19), altering biofilm development (20)(21)(22)(23), and acting as antimicrobial agents against nicheoccupying organisms in the host (24)(25)(26)(27).…”
mentioning
confidence: 99%